2018
DOI: 10.3390/ijerph15030396
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Space-Time Analysis of the 2015 Dengue Outbreak in the Metropolitan Region of Tainan City, Taiwan

Abstract: The metropolitan region of Tainan City in southern Taiwan experienced a dengue outbreak in 2015. This manuscript describes basic epidemiological features of this outbreak and uses spatial and temporal analysis tools to understand the spread of dengue during the outbreak. The analysis found that, independently of gender, dengue incidence rate increased with age, and proportionally affected more males below the age of 40 years but females above the age of 40 years. A spatial scan statistic was applied to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…Area variables are mainly areas where dengue fever has occurred, and it is even more obvious that residents attach great importance to the prevention of dengue fever. Whether in the area where the disease occurs or in the neighbourhood area, people are indirectly alert to the disease [5]. In terms of gender, men and women have different sensitivities to disease prevention.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Area variables are mainly areas where dengue fever has occurred, and it is even more obvious that residents attach great importance to the prevention of dengue fever. Whether in the area where the disease occurs or in the neighbourhood area, people are indirectly alert to the disease [5]. In terms of gender, men and women have different sensitivities to disease prevention.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…In terms of gender, men and women have different sensitivities to disease prevention. Chuang et al [5] found that a relatively high proportion of women are infected with dengue fever. Nielsen et al [51] also pointed out that gender is significant in health risk assessment and has been found to potentially affect the reduction of health risks.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Hainan and Jiangsu are not dengue-prevalent regions (Gao et al, 2010;Lai et al, 2015). However, Guangzhou, Foshan, and Tainan are districts with recent dengue epidemics (Chuang et al, 2018;Wang et al, 2016;Xiao et al, 2016). In the A. albopictus Foshan, A. albopictus Guangzhou, and A. aegypti Taiwan Tainan strains, 8.3%-17.7% of the colonies of gut cultivable bacteria were S. marcescens.…”
Section: S Marcescens Enhances the Vector Competence Of Field Mosquimentioning
confidence: 99%